The Novel Map : Space and Subjectivity in Nineteenth-Century French Fiction - Bray, Patrick M. (Patrick Maxwell) (Book collections on Project MUSE., 2013)
Focusing on Stendhal, Gerard de Nerval, George Sand, Émile Zola, and Marcel Proust, this book explores the ways that these writers represent and negotiate the relationship between the self and the world as a function of space in a novel turned map. With the rise of the novel and of autobiography, the literary and cultural contexts of nineteenth-century France reconfigured both the ways literature could represent subjects and the ways subjects related to space. In the first-person works of these authors, maps situate the narrator within the imaginary space of the novel. Yet the time inherent in the text's narrative unsettles the spatial self drawn by the maps and so creates a novel self, one which is both new and literary. The novel self transcends the rigid confines of a map. In this study, the author charts a new direction in critical theory.